Sensory quality of upcycled legume water: Expectation vs. reality - Hippolite, Lauryn Rose; Feng, Ziqian; Zhang, Yanyu; Lee, Sung Je; Serventi, Luca (Frontiers in Food Science and Technology, 2023)
Aquafaba and liluva are names used to define the processing water of food legumes. Large volumes of liluva are generated by frozen pea manufacturers (blanching water) and tofu producers (tofu whey). Studies have shown the potential of aquafaba and liluva in food applications as texture improvers and sources of bioactive substances and prebiotics. Nonetheless, no information on consumer perception of these new food ingredients is available. Therefore, this study investigated consumer expectations of steam blanching pea water (SBPW) and tofu whey (TW), correlating it with their actual sensory qualities and functional properties. Specifically, liluva was used as a source of prebiotics and hydrocolloids in 3D-printed mashed potatoes to enhance their rheology and printability. A preliminary survey showed a limited understanding of SBPW and TW as food ingredients, with only 43% and 38% of subjects willing to try TW and SBPW, respectively, with most subjects unsure on whether they wanted to or not (34% tofu whey and 49% liluva). Once the actual sensory test was conducted, TW-added mashed potato received favorable scores for all sensory attributes (appearance, aroma, taste, and texture). In contrast, SBPW-added mashed potato had a negative score on the color, as all nine focus group subjects described the color as gray. Overall, TW enhanced the printability of mashed potatoes due to its emulsifying ability and possibly coagulants derived from tofu making, and it was more appreciated sensory-wise, resulting in being the most preferred out of three samples (SBPW, TW, and control). Therefore, emphasizing consumer education may be key when expanding these innovative food ingredients to other food areas.